ANALYSIS OF MARKETING STRATEGIES IN AN EFFORT TO INCREASE TURNOVER OF ORNAMENTAL RESTAURANT IN NGIMBANG, LAMONGAN REGENCY - Mohamad Rizal Nur Irawan (Sean Institute, 2023)
This study aims to find out how the application of SWOT analysis and the increase in turnover was carried out by Bu Juariyah's Restaurant Business, Ngimbang District, Lamongan Regency. The sampling technique in this study is the snowball sampling method, which is a sampling method obtained by rolling from one respondent to another, generally this method is used to explain social or communication patterns (sociometrics) of a particular community. Data analysis was carried out qualitatively through a strategic management concept approach. The results of this study indicate Mrs. Juariyah's restaurant business. From the results of internal factors (IFAS) and external factors (EFAS), the scores can be broken down as follows. Strengths have a total score of 2.44, weaknesses have a total score of 0.78, opportunities have a total score of 2.28, and threats have a total score of 0.64. So it can be seen that the score of strength over weakness is with a difference of (+) 1.66, while the score for opportunity above threat is at odds with (+) 1.64.